Academic roots: the most prolific authors of bibliometrics - Ibrahim S.IIP., M.P, Cecep (Halu Oleo University Kendari, 2024)
The purpose of this study is to discover the academic roots of the world's most prolific authors of bibliometrics research. José Mara Merigó, Lutz Bormann, Yuhshan Ho, and Giovanni Abramo are bibliometric research professionals in Europe and Asia. The research method employs a bibliometric methodology using reference publication year spectroscopy (RPYS). This study has three stages: data collecting, data processing, and outcome analysis. Data is gathered from the Scopus database by entering the topic